Effects of mediastinal irradiation on oesophageal function. (February 1996) - Yeoh, E; Holloway, R H; Russo, A; Tippett, M; Bermingham, H; Chatterton, B; Horowitz, M
Abstract : Although it is well recognised that oesophageal symptoms are common during therapeutic mediastinal irradiation of intrathoracic malignant diseases, the effects of mediastinal irradiation on oesophageal function are poorly defined. To clarify the pathogenesis of these sequelae a prospective study was performed to document comprehensively the effects of mediastinal irradiation on oesophageal function. Oesophageal symptoms, barium swallow, endoscopy, and combined radionuclide scintigraphy and oesophageal manometry were evaluated in eight patients with potentially curable intrathoracic malignant disease before treatment, during the last week of mediastinal irradiation, and six to eight weeks after its completion. Before irradiation, structural abnormalities were excluded by barium swallow and endoscopy. All but one patient experienced odynophagia or dysphagia, or both, during mediastinal irradiation (p < 0.001) but endoscopic abnormalities were observed in only three patients and there was no correlation between oesophageal symptoms and endoscopic changes. Irradiation, however, had no significant effect on oesophageal motility or transit. It is concluded that oesophageal symptoms which develop during mediastinal irradiation are not a result of altered oesophageal motility or transit and may reflect increased mucosal sensitivity.